Mobilizations and Movements of Foreign Fighters from Southeast Asia to Syria and Iraq - Tia Mariatul Kibtiah (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2016)
This article examines foreign fighter movements, in particular those who joined the Islamic State and al-Nusra front from Southeast Asia to Syria and Iraq. It will analyze the dynamics of the movements in Southeast Asia and Syria and Iraq, provide a discussion of the potential threats of the returnees and how state and civil society respond to the threats of the groups. It is based on interviews to Afghan veterans in Indonesia and analyses of primary and secondary sources of the Syrian and Iraq conflicts. It argues that it is urgent to strengthen unity and partnership between state and civil society in coping the rise of the terrorism movements and to prevent violent attacks after the returns of Southeast Asian fighters from Syria and Iraq.